Exploration Utilization of Chatbots Based Artificial Intelligence in Digital Marketing for Snack SMEs Traditional Typical of Sumenep – Madura - Fausi Arifin; Nurul Hidayat; Hairul Rahman; Moh Sofwan Kastir Al Aziz; Khairil Anwar; Buhairi (Universitas KH. Abdul Chalim Mojokerto, 2026)
Study This explore utilization chatbot based Artificial Intelligence (AI) in digital marketing in snack SMEs typical Sumenep Madura which has start adopt technology the However Not yet optimize its use . Through approach qualitative with technique interviews , observations , and documentation , as well as data analysis using NVivo 15 , research This find that chatbot utilized For respond consumer through social media and e-commerce platforms , but its function Still limited to services basis . MSME actors feel a number of benefit like efficiency time , increase speed response , and convenience service customers , but faced with obstacles in the form of low digital literacy , limitations device , instability network , as well as various problem technical aspects of chatbots . In addition , concerns related costs , needs adaptation technology and resistance to change participate influence optimization utilization Chatbot . Consumers and employees hope chatbot features capable give recommendation more personal and interactive products , while MSMEs require integration more systems​ flexible and appropriate with context local . With thus , chatbot based AI own potential significant For strengthening the digital marketing strategy of snack MSMEs typical Sumenep Madura, however required improvement digital literacy , support more technology​ adaptive , as well as development aligned features​ with characteristics business small in area the .